Bending, buckling and linear vibration of bio-inspired composite plates. (1st September 2022) - Mohamed, S.A.; Mohamed, N.; Eltaher, M.A.
Abstract: Biological composite structures with helicoidal schemes and designs have good damage tolerance and high impact energy absorption. However, the effect of redirection and the reorientation of fibers inside the matrix of helicoid structure on their mechanical performance and response have not been comprehensively examined. Therefore, this works aims to cover this topic and investigate the static, buckling and vibration behaviors of laminated composite plate structure with helicoidal orientation scheme for the first time. The formulation and analysis is based on the hypothesis of first order shear deformation theory (FOSDT) of plate. Various sets of laminates including Fibonacci sequence are considered in this study to get the optimum scheme of layer's orientation. Based on energy principle, the governing equations of motion and associated boundary conditions are derived in detail. The obtained partial differential equations of motion, in terms of displacement fields, are solved by two-dimensional differential quadrature method (2D-DQM). Verification with previous works is presented to validate the present mathematical model and solution technique. The influences of different parameters such as laminate sequence, boundary conditions, material and geometric properties on the static, buckling stability and vibration responses of composite plate are studied and discussed. It is found that the laminate sequence has a significant influence on bending, critical buckling and natural frequencies, as well as this effect varies with various aspect ratios and side to thickness ratios, and boundary conditions of the composite plate. Highlights: Developed a mathematical model to predict the dynamic response of bio-inspired composite plates. The geometrical kinematic relations of displacements are portrayed with first order shear deformation plate theory. The integro-differential equations of motion are discretized in spatial direction by using numerical two-dimensional differential quadrature method (2D-DQM). The model can be used in designing of spacecrafts, naval, automotive, see pilers, helicopter and wind turbines with helicoidal schemes.